Analisis Nilai Budaya dan Nilai Sosial pada Tradisi Arak-arakan Rujukan di Kampung Cipeucang sebagai Bahan Pembelajaran Projek Penguatan Profil Pelajar Pancasila (Kearifan Lokal) di SMA - Aulia, Novi (Jurnal Artikula, 2023)
This research aims to describe the cultural values and social values in the reference procession tradition in Cipeucang village as learning material for Pancasila student projects, especially in high school. This research was carried out based on a qualitative approach with descriptive methods that focused on content analysis. The data and data sources in this research are in the form of text, such as: words, phrases, sentences and conversations related to cultural values and social values. The instrument used in this research was the researcher himself with a theory validation test. Based on the description of the results of the analysis of the "reference procession" tradition in Cipeucang village, it contains cultural values, namely that by preserving culture through tradition you can learn a lot about life. This tradition has social values that provide an understanding of social life in society. This research is recommended for consideration as learning material for Indonesian language and literature in order to improve students' ability to understand the cultural and social values of cultures in society, especially traditions and can improve the teaching of literature and culture in schools